Determinação de corantes marcadores do tipo azo e antraquinona em combustíveis por cromatografia líquida com detecção eletroquímica - Trindade, Magno Aparecido Gonçalves [UNESP]; Rinaldo, Daniel [UNESP]; Vilegas, Wagner [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Sociedade Brasileira de Química, 2010)
An analytical method based on high-performance liquid chromatography with electrochemical detection has been developed and applied to the determination of Solvent blue 14 (SA-14) and Solvent red 24 (SV-24) in fuel samples. The dyes were better separated on C18 column, using a mobile phase composed of acetonitrile and ammonium acetate (90:10, v/v). Detection was carried out at an oxidation potential of +0.85V. The detector response was linear at concentration range of 7.50×10-8 - 1.50×10-6 mol L-1 (r = 0.997) for SA-14 and SV-24, respectively. The method was used to quantify these dyes in fuels samples with satisfactory accuracy and precision.
Determination of azo and anthraquinone dyes in fuels sample using hplc with electrochemical detection
Keywords: solvent Blue 14 dye; solvent Red 24 dye; fuel analysis